A review on the mechanical metamaterials and their applications in the field of biomedical engineering - Wang, Hao; Lyu, Yongtao; Bosiakov, Sergei; Zhu, Hanxing; Ren, Yuanfei (Frontiers in Materials, 2023)
Metamaterials are a group of materials/structures which possess novel behaviors not existing in nature. The metamaterials include electromagnetic metamaterials, acoustic metamaterials, mechanical metamaterials, etc. among which the mechanical metamaterials are widely used in the field of biomedical engineering. The mechanical metamaterials are the ones that possess special mechanical behaviors, e.g., lightweight, negative Poisson's ratio, etc. In this paper, the commonly used mechanical metamaterials are reviewed and their applications in the field of biomedical engineering, especially in bone tissue engineering and vascular stent, are discussed.Finally, the future perspectives of this field are given.